Perfil bioquímico das galinhas poedeiras na região de Araçatuba-SP - Barbosa, Tatiana de Sousa [UNESP]; Mori, Carolina Kimie [UNESP]; Polonio, Lorrayne Bernegossi [UNESP]; Giglio Ponsano, Elisa Helena [UNESP]; Ciarlini, Paulo Cesar [UNESP] (Universidade Estadual de Londrina (UEL), 2011)
The establishment of reference values is extremely important for successful diagnosis and treatament. Considering that in most species the serum chemistry profile is influenced by race, climate and management, we decided to determine the values of aspartate aminotransferase (AST), alanine aminotransferase (ALT), uric acid, creatinine, creatine kinase (CK), phosphatase alkaline (ALP), gamma-glutamyltransferase (GGT), total protein (TP) and albumin of Dekalb hens in the region of Araçatuba - SP. All samples were processed soon after harvesting in an automatic biochemical analyzer calibrated and monitored with control serum levels I and II. The following confidence intervals were obtained: 44-65,5 U / L (AST); 18,4-21,2 U / L (ALT), 2.1-2.5 mg / dL (uric acid); 1.7 to 5.7 U / L (CK); CI 1.2-2.2 mg / dL (creatinine), 1276-1506 U / L (FA); 18-23,4 U / L (GGT); 27.12 to 29 g / L (PT), from 11.4 to 12.16 g / L (albumin).

O estabelecimento de valores bioquímicos de referência é de extrema importância para o sucesso do diagnóstico e do tratamento. Considerando que na maioria das espécies o perfil bioquímico sérico sofre influência de raça, clima e manejo, decidiu-se determinar os valores de aspartato aminotransferase (AST), alanina aminotransferase (ALT), ácido úrico, creatinina, creatina quinase (CK), fostatase alcalina (FA), gama-glutamiltransferase (GGT), proteína total (PT) e albumina de galinhas poedeiras da linhagem Dekalb da região de Araçatuba – SP. Todas as amostras foram processadas logo após a colheita em um analisador bioquímico automatizado previamente calibrado e monitorado com soros controles nível I e II. Obtiveram-se os seguintes intervalos de confiança: 44-65,5 U/L (AST); 18,4-21,2 U/L (ALT); 2,1–2,5 mg/dL (ácido úrico) ; 1,7– 5,7 U/L (CK) ; 1,2–2,2 mg/dL (creatinina); 1276–1506 U/L (FA); 18-23,4 U/L (GGT); 27,12– 29 g/L (PT); 11,4 – 12,16 g/L (albumina).
Serum biochemical profile of laying hens in the region of Araçatuba, SP
Keywords: Poultry; Biochemical profile; Analysis; Reference values; Aves; Parâmetros bioquímicos; Análises; Valores de referência